HRM Practices of an International Retailer in Malaysia: Comparing the Perceptions of Subordinates and Supervisors at Six Retail Outlets - Tay, Angeline (Asian Journal of Business and Accounting, 2017)
Past empirical studies on retail businesses have focused on the marketing and consumer behaviour perspectives rather than on the importance of their human capital. This article highlights the extent to which 292 subordinates and 106 of their immediate supervisors perceive that high involvement human resource management practices are implemented at six outlets of a large international retailer in Malaysia. The survey revealed that supervisors mostly rated higher than their subordinates on employees’ ability to participate in decision‐making and training programmes, as well as on the presence of relevant resources, information, and fair rewards across the six outlets. In addition, there were differences in opinions between how employees from the different outlets perceived the extent to which the four components of HRM practices were present in their respective organisations. Keywords: Employee self‐reports, HRM practices, Retailing, Supervisor evaluation